Preparation and characterization of GO/ZnO electrode for supercapacitors - Dung, Hoang Tran; Tung, Doan Thanh; Thanh Tam, Le Thi; Dung, Trinh Quang; Yen, Nguyen Thi; Thanh, Ngo Ba; Dung, Ngo Thanh; Hong, Phan Ngoc; Lu, Le Trong (Vietnam Journal of Science and Technology, 2019)
In this paper, zinc oxide (ZnO) nanoparticles were prepared by solvothermal method. A mixture of ZnO nanoparticles and GO, surfactants, binders are dispersed in aqueous solvent. This suspension was then used as the ink for the modified 3d printer to coat on the graphite substrate to form electrodes. The GO/ZnO film has a specific capacitance of 119.9 F/g at a scan rate of 5 mV/s of CV test. The specific discharge capacitance was 153.9 F/g and retained 94.5% after 3000 cycles of galvanostatic charge-discharge (GCD) measurement with a current density of 15 mA/cm2.